Controlling Rheology of Fluid Interfaces through Microblock Length of Sequence‐Controlled Amphiphilic Copolymers. Issue 18 (4th August 2022) - Yu, Xiaoxi; Li, Guofang; Zheng, Bingqian; Youn, Gyusaang; Jiang, Ting; Quah, Suan P.; Laughlin, Scott T.; Sampson, Nicole S.; Bhatia, Surita R.
Abstract: Previous studies have demonstrated that films of sequence‐controlled amphiphilic copolymers display contact angles that depend on microblock size. This suggests that microblock length may provide a means of tuning surface and interfacial properties. In this work, the interfacial rheology of a series of sequence‐controlled copolymers, prepared through the addition of bicyclo[4.2.0]oct‐1(8)‐ene‐8‐carboxamide (monomer A) and cyclohexene (monomer B) to generate sequences up to 24 monomeric units composed of (A m B n ) i microblocks, where m, n,  and i range from 1 to 6. Interfacial rheometry is used to measure the mechanical properties of an air–water interface with these copolymers. As the microblock size increases, the interfacial storage modulus, G ′, increases, which may be due to an increase in the size of interfacial hydrophobic domains. Small‐angle X‐ray scattering shows that the copolymers have a similar conformation in solution, suggesting that any variations in the mechanics of the interface are due to assembly at the interface, and not on solution association or bulk rheological properties. This is the first study demonstrating that microblock size can be used to control interfacial rheology of amphiphilic copolymers. Thus, the results provide a new strategy for controlling the dynamics of fluid interfaces through precision sequence‐controlled polymers. Abstract : The viscoelasticity and stress relaxation dynamics of fluid interfaces can be controlled through the microblock length of precision amphiphilic copolymers.